The Impact of Increasing Sigma Value on the Performance of the Weapon Production Line at PT. X - Fatmawati, Fatmawati; Sudiarso, Aries; Juprianto; Nugroh, Vicky Aditiyo; Ardhana, Andini Aprilia; Gultom, Rudy AG (SPECTA Journal of Technology, 2023)
PT X is one of the companies that produces the Main Armament System (Alutsista) used by the Indonesian National Army. In an effort to meet the production needs of Assault rifle weapons, PT. X must meet the quality standards set by the Ministry of Defense to support the operational tasks of the Indonesian National Army. This study aims to improve the performance of the weapon production line by measuring and evaluating the amount of sigma value in long-barreled weapons. The method used in this research is DMAIC (Define, Measure, Analyze, Improve, and Control), which is a structured approach to quality improvement. This method is used to address problems that occur on the weapon production line and analyze improvements that can be made to improve production performance. The steps recommended in this study include using the Critical to Quality method to identify the causes of problems that occur in weapon production. Furthermore, the Cause and Effect method is used to rank the most significant causes of problems based on the scores obtained. The 5W+1H method is also used to formulate appropriate improvement proposals based on the ranking results from the Cause and Effect Matrix. Thus, it is expected that an effective improvement proposal can be found to improve the performance of PT. X weapon production line.